125 De Novo Mutations in Genes Regulating Neural Stem Cell Fate in Human Congenital Hydrocephalus. Issue Volume 65:Issue CN(2018)Supplement 1 (16th August 2018) - Furey, Charuta Gavankar; Jin, Sheng Chih; Timberlake, Andrew T; Choi, Jungmin; Zeng, Xue; Nelson-Williams, Carol; Mansuri, Mohammad; Lu, Qiongshi; Duran, Daniel; Panchagnula, Shreyas; Alloco, August; Karimy, Jason K; et al.
Abstract: INTRODUCTION: Congenital hydrocephalus (CH) is a major cause of childhood morbidity and mortality, affecting 1 in 1000 live births and representing up to 3% of all pediatric hospital charges in the USA. Accordingly, CH is a major financial burden on health care systems worldwide, and costs the US health care system alone greater than 2 billion annually. Over the last few decades, there has been little progress in the prevention or treatment of hydrocephalus. Current therapy consists of life-long, catheter-based cerebrospinal fluid (CSF) shunting and endoscopic third ventriculostomy with or without choroid plexus cauterization, invasive surgeries with high rates of failure and morbidity. Understanding critical genetic drivers underlying human CH holds promise for the development of targeted therapies. METHODS: We exome sequenced DNA isolated from 125 patient-parent trios (affected patient and unaffected parents) and an additional 52 probands for a total of 177 non-L1CAM primary CH. Exome-sequencing data from these 440 individuals were then analyzed to identify rare, de novo, and transmitted mutations contributing to CH. Candidate mutations were subsequently confirmed by Sanger sequencing and functionally validated using CRISP/Cas9 gene editing in Xenopus to establish gene causality. RESULTS: Exome sequencing identified 3 novel genes with significant burden of rare damaging de novo or transmitted mutations: TRIM71 ( P = 2.15 × 10 –7 ), SMARCC1 ( P = 8.15 × 10 –10 ), and PTCH1 ( P = 1.06 × 10 –6 ). Additionally, 2 de novo duplications were identified at the SHH locus, encoding the PTCH1 ligand ( P = 1.2 × 10 –4 ). Together, these mutations explain 10% of studied congenital hydrocephalus cases. Strikingly, all 4 genes are required for neural tube development and regulate ventricular zone neural stem cell fate. CONCLUSION: These results implicate impaired neurogenesis and not active CSF accumulation in the pathogenesis of a subset of CH patients, with potential diagnostic, prognostic, and therapeutic ramifications.